Probiotic Lactobacilli Isolated from Kefir Promote Down-Regulation of Inflammatory Lamina Propria T Cells from Patients with Active IBD - Curciarello, Renata; Canziani, Karina E.; Salto, Ileana; Barbiera Romero, Emanuel; Rocca, Andrés; Doldan, Ivan; Peton, Emmanuel; Brayer, Santiago; Sambuelli, Alicia M.; Goncalves, Silvina; Tirado, Pablo; Correa, Gustavo J.; et al. (Frontiers in Pharmacology, 2021)
Ulcerative colitis and Crohn's disease, the two main forms of inflammatory bowel disease (IBD), are immunologically mediated disorders. Several therapies are focused on activated T cells as key targets. Although Lactobacillus kefiri has shown anti-inflammatory effects in animal models, few studies were done using human mucosal T cells. The aim of this work was to investigate the immunomodulatory effects of this bacterium on intestinal T cells from patients with active IBD. Mucosal biopsies and surgical samples from IBD adult patients (n=19) or healthy donors (HC; n=5) were used. Lamina propria mononuclear cells were isolated by enzymatic tissue digestion, and entero-adhesive Escherichia coli-specific lamina propria T cells (LPTC) were expanded. The immunomodulatory properties of L. kefiri CIDCA 8348 strain were evaluated on biopsies and on anti-CD3/CD28-activated LPTC. Secreted cytokines were quantified by ELISA, and cell proliferation and viability were assessed by flow cytometry. We found that L. kefiri reduced spontaneous release of IL-6 and IL-8 from inflamed biopsies ex vivo. Activated LPTC from IBD patients showed low proliferative rates and reduced secretion of TNF-α, IL-6, IFN- and IL-13 in the presence of L. kefiri. In addition, L. kefiri induced an increased frequency of CD4+FOXP3+ LPTC along with high levels of IL-10. This is the first report showing an immunomodulatory effect of L. kefiri CIDCA 8348 on human intestinal cells from IBD patients. Understanding the mechanisms of interaction between probiotics and immune mucosal cells may open new avenues for treatment and prevention of IBD.